Intrinsic and extrinsic correlations of galaxy shapes and sizes in weak lensing data - Ghosh, Basundhara; Durrer, Ruth; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT The subject of this paper is to build a physical model describing shape and size correlations of galaxies due to weak gravitational lensing and due to direct tidal interaction of elliptical galaxies with gravitational fields sourced by the cosmic large-scale structure. Setting up a linear intrinsic alignment model for elliptical galaxies that parametrizes the reaction of the galaxy to an external tidal shear field is controlled by the velocity dispersion; we predict intrinsic correlations and cross-correlations with weak lensing for both shapes and sizes, juxtaposing both types of spectra with lensing. We quantify the observability of the intrinsic shape and size correlations and estimate with the Fisher formalism how well the alignment parameter can be determined from the Euclid weak lensing survey. Specifically, we find a contamination of the weak lensing convergence spectra with an intrinsic size correlation amounting to up to 10 per cent over a wide multipole range (ℓ = 100…300), with a corresponding cross-correlation exhibiting a sign change, similar to the cross-correlation between weak lensing shear and intrinsic shapes. A determination of the alignment parameter yields a precision of a few per cent forecasted for Euclid, and we show that all shape and many size correlations should be measurable with Euclid.